Five Years of Voluntary Refugee Aid in Germany - Kim Bräuer (Comparative Population Studies, 2022)
This article examines voluntary refugee aid from 2015 to 2020, investigating the extent to which volunteers and refugee aid recipients have related their perceptions and emotional interpretations to the welcoming discourse and the local organisation of voluntary refugee aid. The analysis was based on contrasting sample of interviews and newspaper articles and includes a comparison of the politicised metropolitan refugee aid in Berlin with traditional charity-based aid in Braunschweig. It becomes evident that the emotional perceptions of volunteers differ depending on their reason for helping and their previous experiences. In addition, the article suggests that the recipients of refugee aid, most notably shortly after their arrival, do not refer to the welcoming discourse but instead to their own experiences or those of their acquaintances.